The lanthanide tetrad effect in granitoid of the Alvand Intrusive Complex, Hamedan - Farhad Aliani; Zahra Sabouri Ranjbar; Mirmoahmmad Miri (پترولوژی, 2016)
The Alvand Intrusive Complex (AIC) is located in an area between Hamedan and Tuyserkan cities, and crops out over an area 400 km2 intruding the Sanandaj-Sirjan plutono-metamorphic belt. The emplacement age of the AIC is constrained to Upper to Middle Jurassic, based on U–Pb zircon geochronogic data. Lanthanide tetrad effects are often observed in REE patterns in the granites of the Alvand. The degree of the tetrad effect (TE1,3) is estimated and plotted vs. K/Rb, Sr/Eu, Eu/Eu*,Y/Ho, and Zr/Hf. The diagrams reveal that the tetrad effect develops parallel to granite evolution, and significant tetrad effects are strictly confined to highly differentiated samples. The strong decrease of Eu concentrations in highly evolved rocks suggests that Eu fractionates between the residual melt and a coexisting aqueous high-temperature fluid.